A Novel Longline That Can Be Used By a Single Crew in the Aegean Sea: Solo Longline - Cezmi KANÇOBAN (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2020)
This short paper presents an innovation on the use of a bottom longline with only a single crew on a fishing boat in the Aegean Sea. The mainline was 0.80 mm in diameter and 75 m in length, with branch lines of 0.45 mm in diameter and 70 cm in length. Distance between two adjacent branch lines was 7 m. The total duration of the operation, excluding soak time, was 35 minutes for a total of 40 hooks. Although this small prototype seems to succeed, larger versions may cause operational difficulties. Therefore, we suggest that further handling techniques should be developed in the future for challenging tasks such as baiting and solo using.